Types and Effectiveness of Public Policy Measures Combatting Graffiti Vandalism at Heritage Sites - Marko Raič; Daniela Angelina Jelinčić (Heritage)
Graffiti vandalism poses a major threat to cultural heritage. This review paper aims to identify and describe policy measures for combatting graffiti vandalism on heritage assets, which is a significant and complex problem in urban areas worldwide with considerable cultural and economic impacts. Alongside, their effectiveness is assessed. Despite being recognized as a significant problem, research papers addressing graffiti vandalism policies are existent but not adequately systematized. In the first part of this article, a theoretical overview of graffiti vandalism is provided. This is followed by an outline of the research methodology, along with a presentation of results based on the analysis of the reviewed articles. Given the relatively small number of articles that directly address this topic, the review is supplemented with an analysis of best practices, specifically, examining municipal measures and strategies aimed at combating graffiti vandalism.